Development of Integrated Science Worksheet with Immersed Model Based on Corncob Utilization Project to Improve Students’ Creative Thinking Skills - Setiatun, Siti Nur; Diawati, Chansyanah; Fadiawati, Noor (Jurnal Pendidikan MIPA, 2022)
This study aims to develop an Integrated Science Student Worksheet Immersed based on the use of corn cobs to improve the creative thinking skills of junior high school students. This study uses the ADDIE research and development method by Dick and Carry. The results obtained, namely expert validation, showed that the average percentage of the aspect of content conformity to basic competencies was 92.07% and the construction aspect of the student worksheet component was 100% with very high criteria. The effectiveness of student worksheets in terms of n-gain and effect size , respectively, is of 0.93 and 0.95 with large criteria. Based on this, the immersed integrated science student worksheet based on the corn cob processing project is effective for improving the creative thinking skills of junior high school students.Keywords: student worksheets, project-based learning, creative thinking.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp294-303